(untitled) (Journal of Universal Science Research, 2023)
Like every field of education in our country today improvement of the content of special education, innovative practice the issue of introducing technologies is considered urgent. Special education education, upbringing and life of children with developmental problems solves preparation tasks. As you know, one type of development or another organic disorders in brain activity among children with problems As a result, children with certain deviations and deviations in their intellect available, they are educated in specialized educational institutions they get.